SYNTHESIS AND CYTOTOXIC ACTIVITY OF 2,5-BIS(4-BORONIC ACID)BENZYLIDINE CYCLOPENTANONE ON HER2 OVEREXPRESSED-CANCER CELLS - Rohmad Yudi Utomo; Herwandhani Putri; Pudjono Pudjono; Ratna Asmah Susidarti; Riris Istighfari Jenie; Edy Meiyanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Development of chemotherapeutic agent and boron carrying pharmaceutical based on HER2 specific targeted is important due to its role in enhancing cancer progression. The purpose of this study is to synthesize curcumin analogue, namely Pentagamaboron-0 (PGB-0) or 2,5-bis(4-boronic acid)benzylidine cyclopentanone, and to explore the cytotoxic activity on HER2 overexpressed-cancer cells. MCF-7/HER2 was used as a model of HER2 overexpressed-cancer cells and NIH3T3 as normal cells. PGB-0 bound to ATP binding site of HER2 and EGFR based on molecular docking study. PGB-0 was synthesized resulting in 33% yield and was confirmed by IR, 1HNMR, 13CNMR and Mass spectroscopy. Based on MTT assay PGB-0 decreased cells viability on MCF-7/HER2 cells with IC50 value of 270 µM but performed no effect on NIH3T3 cells. Cell cycle analysis revealed that PGB-0 increased sub-G1 accumulation. PGB-0 decreased HER2 expression in a dose-dependent manner. We conclude that the new compound PGB-0 inhibits cell growth through cell death induction and decreased HER2 expression. Thus, PGB-0 is potential to be developed as a chemotherapeutic agent and boron carrying pharmaceutical targeted on the HER2 receptor.